2022
DOI: 10.15178/va.2023.156.e1434
|View full text |Cite
|
Sign up to set email alerts
|

Use of ePortfolios to improve English speaking skills by learners of English as a foreign language

Abstract: High-impact practices (HIPs) have been adopted by many universities around the world to enhance student learning. The aim of this qualitative study is to analyze how building ePortfolios may impact the student learning experience via weekly reflections. A total of 47 senior undergraduate English as a foreign language (EFL) student participants’ shared reflections about their research experiences via the development of ePortfolios. Data analysis was carried out through deductive coding of the transcribed focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Afterward, social networks have been shown to improve students' willingness to read in English and their listening and speech (Cárdenas et al, 2010;Yunita & Maisarah, 2020). Furthermore, several researchers have explored using various social media apps as educational aids for teaching and learning English (Bensalem & Alenazi, 2022;Moreira Aguayo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Afterward, social networks have been shown to improve students' willingness to read in English and their listening and speech (Cárdenas et al, 2010;Yunita & Maisarah, 2020). Furthermore, several researchers have explored using various social media apps as educational aids for teaching and learning English (Bensalem & Alenazi, 2022;Moreira Aguayo et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of pleasure centers in the brain, accompanied by the release of dopamine, a neurotransmitter associated with the sensation of reward and satisfaction, plays an essential role in this process (Schultz, 2016). Numerous studies globally have confirmed that when future educators experience genuine enjoyment while practicing oral expression in English, it creates a conducive environment for developing their language skills (Bensalem, 2022).…”
Section: Introductionmentioning
confidence: 99%